EVALUATING THE IMPACT OF PROBLEM-BASED LEARNING ON MATHEMATICS ACHIEVEMENT - Rifdatul Zahra; Asih Mardati; Yeyen Febrilia (STKIP Singkawang, 2026)
Mathematics is often perceived as a challenging subject by many elementary school students due to its abstract nature and the limited use of contextual learning approaches. This study aimed to investigate the effect of Problem-Based Learning (PBL) on students' mathematics achievement in fraction topics. A quasi-experimental design with a non-equivalent control group was employed involving 36 fifth-grade students at SD Muhammadiyah Noyokerten. The participants were assigned to an experimental group receiving PBL instruction and a control group receiving conventional instruction. Data were collected using pretests and posttests and analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test. The results indicated significant improvements in mathematics achievement in both groups, with the experimental group demonstrating a substantially greater increase in mean scores (from 53.33 to 82.22) than the control group (from 62.78 to 72.78). These findings suggest that Problem-Based Learning is associated with greater improvements in elementary students' mathematics achievement, particularly in learning fractions